Cover Feature: Crystallites and Electric Fields in Solid Ammonia (ChemistryOpen 10/2020) - Cassidy, Andrew (ChemistryOpen, 2020)
The Cover Feature shows films of solid ammonia containing spontaneously generated electric fields when prepared by vapour condensation. Dipole moments of ammonia molecules spontaneously orient such that films harbour electric fields in excess of 10(8)V m(‐1)immediately upon growth. The results demonstrate that ammonia crystallises into two distinct polymorphs, one below growth at 55 K and a second above 55 K, and allow us to set an upper limit for the size of the exciton and, in turn, the size of the crystallites. More information can be found in the Full Paper by Andrew Cassidy et al.[Image: see text]